The importance of thermal and topographic forcing for the European climate - Ager-Wick, Anita (2008)
In this thesis I have studied several factors influencing the time average atmospheric circulation. The study introduced changes to the thermal and orographic forcing by altering and removing the heat sources and topography. The particular focus has been on Europe and the North Atlantic, to understand better what determines Europe's wintertime climate. The model used in my work is the NCAR CAM3 model, in default and slab ocean model (SOM) mode. I did one control run and five modified runs, checking for the climatic effect of both the ocean and atmosphere. In the first modified run, I removed the surface temperature signature due to the ocean surface currents, and in the next run I removed the topography of the northern hemisphere. I then conducted two more runs similar to these two: one with zonal SST's, but with extended sea-ice cover, and another with altered topography in North America. Finally, the model was run in SOM mode and the ocean heat transport was shut-off. The orientation of the isotherms of sea surface temperature SST, and the presence of topography have only a weak effect on the temperature of Europe. Sea-ice proved to have a dramatic cooling effect and the oceanic heat transport keeps the Nordic Seas ice free. This means that although OHT only accounts for about one fifth of the total heat transport, it is crucial for European climate.